2015
DOI: 10.1007/s10973-015-4878-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the rheological behavior and viscosity of decorated multi-walled carbon nanotubes with TiO2 nanoparticles/water nanofluids

Abstract: The effects of temperature and concentration on the flow behavior and viscosity of nanofluids containing TiO 2 nanoparticles, pristine MWCNTs, oxidized MWCNTs and decorated MWCNTs with TiO 2 nanoparticles are experimentally investigated. The results of rheological characteristics of nanofluids revealed that nanofluid of TiO 2 nanoparticle and MWCNT-TiO 2 exhibits shear thickening or dilatant behavior. In contrast, nanofluids containing pristine and oxidized MWCNTs depict the shear thinning or pseudoplastic beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 36 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…It was observed that nanofluids exhibited both non-Newtonian and Newtonian behavior. The viscosity of a Newtonian fluid depends on the shear rate, whereas the non-Newtonian fluid shows a completely different rheological behavior [11,13,17].…”
Section: Fitting Of Empirical Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that nanofluids exhibited both non-Newtonian and Newtonian behavior. The viscosity of a Newtonian fluid depends on the shear rate, whereas the non-Newtonian fluid shows a completely different rheological behavior [11,13,17].…”
Section: Fitting Of Empirical Formulasmentioning
confidence: 99%
“…In addition, the viscosity of a nanofluid shows significant influence on the heat transfer enhancement, and many researchers focused their interests in the nanofluid viscosity, and they found that the viscosity of the nanofluid was affected by the nanoparticle size, volume fraction, shear rate, temperature, and aggregate size. Abbasi et al [11] investigated rheological behaviors of various nanofluids. They found that high portion of multi-walled carbon nanotubes (MWCNTs) resulted in high viscosity of the MWCNT-TiO 2 nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the numerous heat transmission properties, this class of fluids is excessively used in industrial and engineering applications such as cooling of electronic equipment, cooling process in HVAC systems, refrigeration processes, food industry, solar collectors and micro channel heat sink etc. 2 – 5 . Solar collectors are the devices that convert the solar energy into heat energy in eco-friendly and convenient way.…”
Section: Introductionmentioning
confidence: 99%
“…There are many debates on the rheological properties of the nanoflu- www.nature.com/scientificreports/ ids containing carbon nanotubes (CNTs). While some researchers reported that CNT-based nanofluids show non-Newtonian behavior 46 , there are other researchers who observed that the CNT-based nanofluid with the solid concentrations less than 0.5 vol% show Newtonian behavior [47][48][49] , and increasing the solid concentration leads to changing the rheological behavior from Newtonian to non-Newtonian 50 . Thus, in the present study, the rheological properties of the studied nanofluid have been investigated over a different range of shear rates (100-800 1/s), temperatures, and solid concentration to realize that whether the studied nanofluid is a Newtonian or a non-Newtonian fluid.…”
Section: Rheological Behaviormentioning
confidence: 99%